Inhibitory effect of super‐hydrophobicity on silver release and antibacterial properties of super‐hydrophobic Ag/TiO2 nanotubes. Issue 5 (20th May 2015) - Zhang, Licheng; Zhang, Lihai; Yang, Yun; Zhang, Wei; Lv, Houchen; Yang, Fei; Lin, Changjian; Tang, Peifu
Abstract: The antibacterial properties of super‐hydrophobic silver (Ag) on implant surface have not yet to be fully illuminated. In our study, we investigate the protective effects of super‐hydrophobic coating of silver/titanium dioxide (Ag/TiO2 ) nanotubes against bacterial pathogens, as well as its pattern of Ag release. Ag/TiO2 nanotubes are prepared by a combination of electrochemical anodization and pulse electrodeposition. The super‐hydrophobic coating is prepared by modifying the surface of Ag/TiO2 nanotubes with 1H, 1H, 2H, 2H‐perfluorooctyl‐triethoxysilane (PTES). Surface features and Ag release are examined by SEM, X‐ray photoelectron spectroscopy, contact‐angle measurement, and inductively coupled plasma‐mass spectrometry (ICP‐MS). The antibacterial activity of super‐hydrophobic coating Ag/TiO2 nanotubes is investigated both in vitro and in vivo . Consequently, the super‐hydrophobic coating on Ag/TiO2 nanotubes shows a regularly arranged structure; and nano‐Ag particles (10–30 nm) are evenly distributed on the surface or inside the nanotubes. The contact angles of water on the super‐hydrophobic coating Ag/TiO2 nanotubes are all above 150°. In addition, the super‐hydrophobic character displays a certain conserved effect that contributes to the sustained release of Ag. The super‐hydrophobic Ag/TiO2 nanotubes are also effective in inhibiting bacterial adhesion, killing the adhering bacteria and preventing postoperative infection in rabbits. Therefore, it is expected that the super‐hydrophobic Ag/TiO2 nanotubes which can contain the release of Ag, leading to stable release, may show a consistent surface antibacterial capability. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1004–1012, 2016.